Fungal monitoring in an exhibition room with Egyptian mummies in the Museum of Natural Sciences of La Plata, La Plata, Argentina - Nitiu, Daniela Silvana (2018)
The cultural properties kept in museums are exposed to different environmental and biological factors that may affect their aesthetic or structural integrity due to the biodeterioration of their substrates. The aims of the present study were i) to determine the environmental fungal load present both inside and outside the Egyptian Room of the Museum of Natural Sciences of La Plata, Argentina, as well as inside two showcases where Egyptian sarcophagi are preserved, along a one-year monitoring, and ii) to evaluate the possible impact of temperature and relative humidity on the preservation of these mummies. The fungal load was determined by means of a volumetric air sampling methodology and the environmental variables by means of specific instruments. The fungal load found in the four sites studied was of 985,308.7 colony-forming units/m3, belonging to 21 fungal taxa, mainly to the phylum Ascomycota. Eleven of these taxa, among which the most representative were Beauveria bassiana, Fusarium oxysporum, Penicillium sp. and Rhodotorula sp. (as a yeast representative), were common to the four sites, showing a significant similarity between the outdoor and indoor environments. Regarding the environmental variables, the temperature of the exhibition room and that of the two showcases were either similar or lower than the values recommended by the UNI 10829:1999 standards. In contrast, throughout the year, the relative humidity recorded was higher than the recommended values. Continuous studies like the one performed here are key to ensure the preventive conservation of the cultural heritage kept in museum exhibition spaces.